A Comparative Study of Two Scales for Foreign Language Classroom Enjoyment. Issue 5 (October 2019) - Jin, Yinxing; Zhang, Lawrence Jun
This article reports on a study that tested Jin and Zhang's Chinese version of the Foreign Language Enjoyment Scale for classroom learning through confirmatory factor analysis and compared the resulting scale with Li, Jiang, and Dewaele's 11-item scale. Four hundred five Chinese first language senior high school students of English in years 1–3 participated in this study. We found that Jin and Zhang's version of the Foreign Language Enjoyment Scale could be reduced to a 16-item scale that preserved the same factor structure as the original scale. This revised 16-item scale showed a more solid dimensional division and better psychometric properties than Li et al.'s scale. We discussed our findings in relation to the scale's wider application for improving foreign language teaching and learning.